Fathered by God : [learning what your dad could never teach you] - Eldredge, John, 1960- (Nashville : Thomas Nelson, 2009)
In this life-changing message from Eldredge, readers discover a paradigm-shifting path to manhood. The author unveils the six stages many men miss, stages they must complete in order to become the men God designed them to be.
Masculine journey -- True son of a true father -- Boyhood -- Cowboy -- Warrior -- Lover -- King -- Sage -- Let us be intentional.
"Learning what your dad could never teach you"-- Cover.
Keywords: Christian men -- Religious life; Masculinity -- Religious aspects -- Christianity